MICRO, SMALL AND MEDIUM ENTERPRISES ACCESS TO FINANCE CHALLENGES IN SUPPLY SIDE PERSPECTIVE IN ETHIOPIA - Wajebo, Temesgen Woldamanuel (International Journal of Small and Medium Enterprises, 2022)
Empirical evidence shows that the contribution of Micro, Small and Medium Enterprises Empirical evidence shows that the contribution of Micro, Small and Medium Enterprises (MSMEs) to gross domestic product growth, job creation, and poverty alleviation is high. Because of limited access to finance and other factors, a significant number of MSMEs, particularly in developing countries, cannot realize their full potential. The study investigates the micro, small, and medium enterprises' access to finance challenges from the supply-side perspective in Ethiopia. The study employed descriptive analysis using survey data collected from purposely selected 11 banks and 9 micro-finance institutions (MFI). The results show that the lack of collateral, unavailability of financial records, poor pre-loan savings, low loan repayment rate, business feasibility problems, credit information asymmetry, attitudinal problems of the MSMEs, and diversion of the loan are demand-side constraints. From the financial institution’s perspective, the result shows that the liquidity problem, the influence of unfair competition from government banks, the lack of competent human resources, political leaders’ intervention, especially in MFI, corruption, the COVID-19 pandemic, political instability, and inadequate capital are major obstacles. Macroeconomic conditions related to challenges such as foreign exchange shortages, inflation, and trade imbalances are also mentioned as major obstacles. According to the findings of this study, designing and implementing business skill development in mindset, business planning, business bookkeeping, and financial reports can help MSMEs access loans. For financial institutions, the study suggests cash flow-based lending products, applying psychometric testing for credit scoring, improving the governance of the government-affiliated MFIs, and automating the MFIs.JEL Classification Codes: G21, G23,  G32.